Surface electromyography analysis of three squat exercises - Monajati, A.; Larumbe-Zabala, E.; Goss-Sampson, M.; Naclerio, F. (Journal of Human Kinetics, 2019)
The aim of this study was to perform an electromyography comparison of three commonly used lower limb injury prevention exercises: a single-leg squat on a bench (SLSB), a double-leg squat (DLS) and a double-leg squat on a BOSU® balance trainer (DLSB). After determining the maximum isometric voluntary contraction of the hamstring and quadriceps, eight female athletes performed 3 repetitions of each exercise, while electromyography activity of the biceps femoris (BF), semitendinosus (ST), vastus lateralis (VL) and vastus medialis (VM) was monitored. Comparisons between exercises revealed higher activation in BF (descending phase: p = 0.016, d = 1.36; ascending phase: p = 0.046, d = 1.11), ST (descending phase: p = 0.04, d = 1.87; ascending phase: p = 0.04, d = 1.87), VL (ascending phase: p = 0.04, d = 1.17) and VM (descending phase: p = 0.05, d = 1.11; ascending phase: p = 0.021, d = 1.133) muscles for the SLSB compared to the DLSQ. Furthermore, higher muscular activation of the ST (ascending phase: p = 0.01, d = 1.51; descending phase: p = 0.09, d = 0.96) and VM (ascending phase: p = 0.065, d = 1.03; descending phase: p = 0.062, d = 1.05) during the SLSB with respect to the DLSB was observed. In conclusion, the SLSB elicits higher neuromuscular activation in both hamstring and quadriceps muscles compared to the other two analysed exercises. Additionally, the higher muscle activation of both medial muscles (ST and VM) during the SLSB suggests that single leg squatting exercises may enhance lower limb medial to lateral balance, and improve knee stability in the frontal plane.